2015
DOI: 10.1016/j.jhazmat.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the alga Pseudokirchneriella subcapitata to long-term exposure to metal stress

Abstract: The green alga Pseudokirchneriella subcapitata has been widely used in ecological risk assessment, usually based on the impact of the toxicants in the alga growth. However, the physiological causes that lead algal growth inhibition are not completely understood. This work aimed to evaluate the biochemical and structural modifications in P. subcapitata after exposure, for 72 h, to three nominal concentrations of Cd(II), Cr(VI), Cu(II) and Zn(II), corresponding approximately to 72 h-EC10 and 72 h-EC50 values and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 56 publications
(77 reference statements)
3
18
0
2
Order By: Relevance
“…The freshwater alga Pseudokirchneriella subcapitata is highly sensitive to heavy metals ; therefore, it is frequently used as a standard organism in toxicological tests . Cd, Co, Cr, Cu, Mn, and Zn had a detrimental effect on cell structure and metabolism of P. subcapitata . Bossuyt and Janssen observed an increase of chlorophyll and carotenoids content, and a decrease of biomass of P. subcapitata exposed to 0.007–1.6 μmol L −1 Cu.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The freshwater alga Pseudokirchneriella subcapitata is highly sensitive to heavy metals ; therefore, it is frequently used as a standard organism in toxicological tests . Cd, Co, Cr, Cu, Mn, and Zn had a detrimental effect on cell structure and metabolism of P. subcapitata . Bossuyt and Janssen observed an increase of chlorophyll and carotenoids content, and a decrease of biomass of P. subcapitata exposed to 0.007–1.6 μmol L −1 Cu.…”
Section: Introductionmentioning
confidence: 95%
“…Machado et al reported that Cd, Cr, Cu, and Zn have different effects on growth, cell division, and cell volume of P. subcapitata , suggesting that distinct mechanisms underlie the action of each metal. The 72 h exposure of the alga to 1.9 μmol L −1 Cd, 41 μmol L −1 Cr, 1.3 μmol L −1 Cu, and 2.5 μmol L −1 Zn resulted in a severe perturbation of the cell physiological status by loss of membrane integrity, reduction of chlorophyll a content, and the maximum quantum yield of photosystem II, inhibition of esterase activity, and alteration of mitochondrial membrane potential . Soto et al also reported a significant decrease in chlorophyll a in algal cells exposed to 1.2 μmol L −1 Cu and 1.1 μmol L −1 Zn.…”
Section: Introductionmentioning
confidence: 97%
“…Devido a esta característica, Machado et al (2015) escolheu a P. subcapitata para estudar a sua resposta a longos períodos de exposição ao estresse de metais. O estudo partiu de dados existentes indicativos de que esta alga verde é amplamente usada em avaliação de risco ecológico, com base nas características de crescimento da mesma.…”
Section: Pseudokirchneriella Subcapitataunclassified
“…O estudo partiu de dados existentes indicativos de que esta alga verde é amplamente usada em avaliação de risco ecológico, com base nas características de crescimento da mesma. Machado et al (2015), por sua vez, quiseram identificar as causas fisiológicas responsáveis por inibir o crescimento das algas expostas a metais. Para todos os metais testados, foi constatada a inibição da atividade de esterase, variando conforme à dose aplicada.…”
Section: Pseudokirchneriella Subcapitataunclassified
“…As a rule, at first, there is a nonspecific reaction, typical for any irritations. For most of the cells, there is a change of cell membrane permeability during the action of metal ions [2] and subsequent activation of intracellular systems aimed at the suppression of stress reactions and stabilization of intracellular metabolism [3]. For example, in the presence of calcium ions at the initial stage is an activation of different intracellular systems: protein kinases, phospholipases, protein biosynthesis systems, phosphodiesterase, cyclic nucleotides, adenylatecyclase, a contractile apparatus of the cell, etc.…”
Section: Introductionmentioning
confidence: 99%